Illicit drugs and their association with tobacco and alcohol use in adolescents and young schoolchildren - Vanessa Barros de Oliveira, Jéssica; Cappato de Araújo, Rodrigo; Barreto Cunha, Samara; Mola, Rachel; Carolina Rodarti Pitangui, Ana (O Mundo da Saúde, 2020)
The use of psychoactive drugs is generally preceded by the use of alcohol and tobacco, increasing the potential to cause damage to the health and quality of life of adolescents and young adult students. The aim of the present study was to determine the prevalence of illicit drug use and its association with the use of tobacco and alcohol in adolescents and young schoolchildren in the city of Petrolina, PE. This was an epidemiological, school-based, descriptive, correlational, and cross-sectional study, carried out in state public schools, with students aged 12 to 24 years old. A socioeconomic survey and the Youth Risk Behavior Survey (YRBS) were applied to assess risk behaviors. Descriptive analysis, Chi-squared test and Poisson regression were performed to assess the Prevalence Ratio (PR). In all analyses, a significance level of p <0.05 was adopted. 1,326 students were evaluated. Of the total eligible students (n=1,275), 12.9% reported having used an illicit drug during their lifetime. In the regression analysis, the use of illicit drugs was associated with tobacco use (PR 2.95 [1.94-4.50]), binge drinking (PR 2.13 [1.42-3.18]) and higher maternal education (PR 1.69 [1.12-2.55]). The use of illicit drugs had an important prevalence and was significantly associated with the use of tobacco, episodes of binge drinking and with the level of maternal education.